Law and colonial cultures: Legal regimes in world history, 1400-1900 - Benton, Lauren A (Cambridge University, 2013)
Law and Colonial Cultures advances a new perspective in world history, arguing that cultural practice and institutions - not just the global economy - shaped colonial rule and the international order. The book examines the shift from the multicentric law of early modern empires to the state-centered law of high colonialism. In the early modern world, the special legal status of cultural and religious minorities provided institutional continuity across empires. Colonial and post-colonial states developed in the nineteenth century in part as a response to conflicts over the legal status of indigenous subjects and cultural others. The book analyzes these processes by juxtaposing discussion of broad institutional change with microstudies of selected legal cases.